Unveiling Critical Innovation Factors in Sustainable Coffee Production: A Colombian Perspective - Ramirez-Zuñiga Eyder James; Castro-Silva Hugo Fernando; Velásquez-Pérez Torcoroma; Garcia-Cruz Ehidy Karime (Production Engineering Archives)
The coffee sector stands as a cornerstone of Colombia’s economy, ranking third in the nation’s export portfolio. Despite the Colombian coffee esteemed global reputation, it has yet to fully exploit its potential for diversification into differentiated products. Present agro-industrial paradigms emphasize trade and sustainable, efficient agricultural practices, underscoring the imperative for innovation across production, marketing, and distribution channels. This study aims to pinpoint the pivotal innovation factors within coffee farm production processes. To this end, a sample of 66 coffee farms was selected through simple random sampling. Drawing from the 2018 Oslo model, innovation types associated with sustainable specialty coffee certifications were delineated. Within this framework, seven fundamental factors emerged for investigation: economic, social, environmental, production, knowledge, technology, and change management. Through cluster analysis, it became evident that economic, environmental, knowledge, technological, and change management factors are indispensable for fortifying the coffee industry.